8.42. Rozwiąż równanie: a) ( (x – 1) ^ 3 + 35 = 4 * (x + 1) ^ 2 – (2 – x)(4 + 2x + x ^ 2) b) (2 + x) ^ 3 + 9x = 10 – (2 – x) ^ 3 + (2x – 1) ^ 2 c) 2 * (3x – 5) ^ 2 + 3(x + 1) * (x ^ 2 – x + 1) = (x + 3) ^ 3 + 2x * (x ^ 2 – 25) + 72 d) (x – 4) ^ 3 – 12 * (x + 2) ^ 2 + 20x * (x – 4) = – 9 – (x ^ 2 + 3x + 9)(3 – x) .

 8.42. Rozwiąż równanie: a) ( (x – 1) ^ 3 + 35 = 4 * (x + 1) ^ 2 – (2 – x)(4 + 2x + x ^ 2) b) (2 + x) ^ 3 + 9x = 10 – (2 – x) ^ 3 + (2x – 1) ^ 2 c) 2 * (3x – 5) ^ 2 + 3(x + 1) * (x ^ 2 – x + 1) = (x + 3) ^ 3 + 2x * (x ^ 2 – 25) + 72 d) (x – 4) ^ 3 – 12 * (x + 2) ^ 2 + 20x * (x – 4) = – 9 – (x ^ 2 + 3x + 9)(3 – x) .